The Annoying Calls Behavior among a Sample of Students from Al-Quds University - Palestine - Abu fakheda, Juma Barakat (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to study the Annoying Calls Behavior among a sample of students from Al-Quds University - Al-Quds City. And the results of the study showed that there was a high level of Annoying Calls Behavior, with a value of (38.01%), a low level of (22.2%), and there were (39.7%) of them with moderate behavior, The results also showed that there were statistically significant differences between males and females on the total degree of Annoying Calls Behavior in favor of males. The results did not show statistically significant differences between students with scientific and literary specializations. While the results showed that there were statistically significant differences between smoking and non-smokers students on the total degree of Annoying Calls Behavior and the dimensions of entertainment, imitation, sadism and satisfactory compensation. On the sadism dimension in favor of the non-religious, while there were no differences on each of the total degree and dimensions of entertainment, imitation, sexual discharge and satisfactory compensation. The results showed that there were no differences indicative of the total degree of Annoying Calls Behavior, dimensions of amusement, imitation, sexual discharge, sadism, and satisfactory compensation due to both the education of the father and mother, Finally, the results showed that smoking is the only variable that predicts Annoying Calls Behavior, as student smokers are more adverse than non-smokers.